Clinical spectrum of fetal long QT syndrome: a single-center experience. (17th October 2014) - Flöck, A.; Herberg, U.; Gembruch, U.; Merz, W. M.
Abstract: Objective : A considerable proportion of unexplained intrauterine fetal deaths are attributed to long QT syndrome (LQTS) susceptibility. Additionally, the estimated prevalence of LQTS in newborns is 1 in 2000. Still, prenatal diagnosis of LQTS is very rare. The aim of this study was to assess the frequency of prenatal diagnosis of LQTS at our institution, present the cases, compare our findings with the existing literature and propose a possible screening approach. Methods : We searched our fetal database between 2006 and 2013 for cases with suspected diagnosis of LQTS. Results : During the investigation period around 26 000 fetuses were evaluated and three cases of suspected fetal LQTS identified. Two cases of familial LQTS had no or mild intrauterine manifestation of the condition, the third fetus had a de-novo mutation with severe, early-onset disease. Conclusions : LQTS continues to be a challenging prenatal diagnosis. In fetuses who present with complex arrhythmias, a high degree of suspicion is required, and close surveillance and timely delivery in the presence of a multidisciplinary team are necessary. For asymptomatic cases or screening purposes, routine fetal heart rate registration and detailed assessment of cases with a low for gestational age baseline may be an option.